CURTAILING ACCESS TO MEDICINES: DRAWBACKS OF DRAFT PATENTS (AMENDMENT) RULES,2023 - Raghuvanshi, Shivam (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Patent opposition has been an important tool in the arsenal of civil societies and generic companies ensuring increasing access of medicines to the public. Indian Patent law provides for two-tier opposition mechanism: pre-grant opposition where an application for patent has been published but a patent has not been granted, and post-grant opposition can be filed after grant of patent but before expiry of one month. The present paper critically examines the role of patent opposition to safeguard access to medicines in India. It further examines how patent opposition serves as an important mechanism to ensure quality of pharmaceutical patents in the country. Undeserving patents, granted without effective opposition mechanisms, may lead to monopolies, and restrict competition, negatively impacting medicine availability and affordability. The paper explores the impact of patent opposition on medicine access, emphasizing its potential to enhance availability and affordability of medicines. Through legal analysis, case studies, and policy evaluations, the paper aims to provide an in-depth understanding of how patent opposition contributes to safeguarding medicine access, and try to find solution to challenges posed to these provisions from activists supporting stronger patent rights. Following the introduction, paper is divided into four parts. Part 1 discusses patent opposition mechanism under Indian Patent Law. Part 2 covers international agreements and national regulations governing patent opposition. Part 3 focuses on impact of patent opposition on medicines access with special focus on recent ruling of Indian Patent Office in rejection of secondary patent to the bedaquiline drug. Part 4 examines the proposed changes in patent opposition provisions, and how it might play a role in shaping the future of medicine accessibility to public in India.